Anticipating Bullying Against Ja'far Muslim Lingga Tiga Junior High School - Yogi Nanda Saputra; Abdul Halim; Meisa Fitri Nasution (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
In the midst of the rapid development of information and communication technology, it is undeniable that children who are still in school can access a lot of extensive information, one of which is about the problem of bullying. at school. Bullying behavior that occurs in schools is very diverse ranging from physical bullying, verbal bullying, social bullying and cyberbullying. The role of teachers in schools is also very important to minimize bullying in schools. In this research, the researcher distributed a questionnaire to be filled out by the socialization participants with a choice of answers agreeing or disagreeing. Researchers also during the socialization process gave several questions about bullying behavior to obtain supporting results regarding bullying behavior. The results of the research achieved in this study were that all socialization participants already knew what bullying was and it could be concluded that bullying is an action that students should avoid when at school because bullying can have a serious effect on victims of bullying.